Maternal exposure to glyphosate‐based herbicide promotes changes in the muscle structure of C57BL/6 mice offspring. Issue 11 (11th April 2022) - Barbosa, Ariadne; Zazula, Matheus Felipe; Oliveira, Mylena Campos de; Teleken, Jakeline Liara; Costa, Rose Meire; Bonfleur, Maria Lucia; Torrejais, Marcia Miranda
Abstract: Glyphosate (GBH) is a worldwide consumption pesticide and is used in the formulation of Roundup®, one of the most commercialized herbicides in the world. Maternal exposure to this herbicide can promote changes and adaptations in the offspring; however, the effects on skeletal muscle are poorly understood. In this sense, the present study sought to evaluate the effect of exposure to GBH on the characteristics of the soleus (SOL) and extensor digitorum longus (EDL) muscles. C57BL/6 pregnant female mice were divided into two groups: control (CTL) receiving water and glyphosate (GBH; n = 6) receiving 0.5% glyphosate. Male puppies were designated according to the group to which the mothers belonged, such as CTL‐F1 and GBH‐F1 and then euthanized at 150 days of age. There was a reduction in body weight and nasoanal length of animals exposed to GBH, while there was an increase in EDL weight, reduction in the proportion of fibers and number of nuclei, and an increase in the connective tissue of the SOL. The animals exposed to GBH presented higher values of body characteristics, mainly adiposity gain, while they presented a reduction in neuromuscular junctions (NMJ), and an increase in fibrosis in the SOL muscle, while there was a reduction in the number of nuclei, and an increase in the weight of the EDL muscle. These findings indicate that glyphosate can promote changes in the offspring's body growth, the deposition of adipose panicles and its effects on muscle can lead to changes in the structure and functioning of this tissue.